(untitled) (TAMADDUN NURI JURNALI, 2025)
The article describes the consequences and harms of corruption, including bribery crimes, the specific importance of combating such crimes, as well as the work carried out in the field of combating corruption in our country, the innovations introduced in the legislation in this regard and proposals for the implementation of additional measures for their further strengthening.